2020
DOI: 10.3390/ijms21062109
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Dependent Calpain Activation-Mediated Mitochondrial Dysfunction and Oxidative Stress Are Required for Cytotoxicity of Epinecidin-1 in Human Synovial Sarcoma SW982 Cells

Abstract: Synovial sarcoma is a rare but highly malignant and metastatic disease. Despite its relative sensitivity to chemotherapies, the high recurrence and low 5-year survival rate for this disease suggest that new effective therapeutic agents are urgently needed. Marine antimicrobial peptide epinecidin-1 (epi-1), which was identified from orange-spotted grouper (Epinephelus coioides), exhibits multiple biological effects, including bactericidal, immunomodulatory, and anticancer activities. However, the cytotoxic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Cell shrinkage was observed after exposure to TP4 or stausporine; however, only exposure to TP4 increased the percentage of cells with incorporated PI (Figure 2A). Release of cyclophilin A into culture supernatant can serve as a marker for necrotic cell death [22,26], and we found that TP4 increased cyclophilin A in the supernatant, but not the apoptotic marker, caspase-3, in the lysate (Figure 2B). Furthermore, both GSK'872 and Necrostain-1 (necrotic inhibitors) effectively suppressed TP4-induced cytotoxicity in SW982 (Figure 2C,D) and Aska-SS cells (Figure 2E,F).…”
Section: Tp4 Induces Necrotic Cell Death In Human Synovial Sarcoma Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…Cell shrinkage was observed after exposure to TP4 or stausporine; however, only exposure to TP4 increased the percentage of cells with incorporated PI (Figure 2A). Release of cyclophilin A into culture supernatant can serve as a marker for necrotic cell death [22,26], and we found that TP4 increased cyclophilin A in the supernatant, but not the apoptotic marker, caspase-3, in the lysate (Figure 2B). Furthermore, both GSK'872 and Necrostain-1 (necrotic inhibitors) effectively suppressed TP4-induced cytotoxicity in SW982 (Figure 2C,D) and Aska-SS cells (Figure 2E,F).…”
Section: Tp4 Induces Necrotic Cell Death In Human Synovial Sarcoma Cellsmentioning
confidence: 89%
“…The Aska-SS human synovial sarcoma cell line was purchased from RIKEN BioResource Research Center (Koyadai, Ibaraki, Japan). SW982 cells were cultured as described previously [ 26 ]. Aska-SS cells were maintained in Dulbecco’s Modified Eagle’s medium (DMEM; ThermoFisher), supplemented with 20% fetal bovine serum (Biological Industries; Cromwell, CT, USA) and penicillin-streptomycin (Biological Industries; Cromwell, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…22 This issue has been found specifically in SSs. 23 Besides, considering the 75% expression of PD-L1 on SS cells, one might assume that this modality might be applied in the future for primary intracranial SSs. 24 Current literature has noted that the immunotherapy results can be improved by improving mitochondria biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current understanding of cancer cells has highlighted the importance of mitochondria in cancer biogenesis 22 . This issue has been found specifically in SSs 23 . Besides, considering the 75% expression of PD‐L1 on SS cells, one might assume that this modality might be applied in the future for primary intracranial SSs 24 .…”
Section: Discussionmentioning
confidence: 99%
“…36) Excessive calcium induces calpain activation. 37) Therefore, we hypothesized that CVB3 infection could activate calpain. In our previous studies, we have demonstrated that calpain was activated during CVB3 infection.…”
Section: Discussionmentioning
confidence: 99%